Peroneal electrical transcutaneous neuromodulation in the home treatment of the refractory overactive bladder - Krhut, Jan; Rejchrt, Michal; Slovak, Martin; Dvorak, Roman V; Grepl, Michal; Zvara, Peter (International urogynecology journal, 2023)
INTRODUCTION AND HYPOTHESIS: The aim of this prospective, open-label, multicenter, noncomparative study was to evaluate the efficacy and safety of peroneal electrical transcutaneous neuromodulation (peroneal eTNM®) using the URIS® neuromodulation system as a home treatment for refractory overactive bladder (OAB). METHODS: The patients were treated with daily peroneal eTNM® for 30 min over a 6-week period. The primary endpoint was defined as the proportion of responders, i.e., participants with ≥ 50% reduction in the average daily sum of severe urgency episodes (defined as "I could not postpone voiding but had to rush to the toilet in order not to wet myself") and urgency incontinence episodes. In addition, bladder diary variables, symptom severity (OAB V8 questionnaire), treatment satisfaction (visual analog scale), and pain perception (visual analog scale) were evaluated at baseline (BL), at week 4 (W4), and at the end of treatment (EoT). Safety evaluations included monitoring of the incidence and severity of adverse events (AEs). Changes in time were analyzed using the nonparametric one-way ANOVA Friedman test for categorical variables and the Wilcoxon rank-sum test for the noncategorical variables. RESULTS: In total, 40 subjects were screened and 29 were included in the full analysis set. The proportion of responders was 86% at W4 and 79% at EoT. There was a significant reduction in frequency (p<0.001), number of severe urgency episodes (p< 0.001), number of urgency incontinence episodes (p=0.001), and number of nocturia episodes (p=0.002). There was a significant improvement in the OAB V8 score and treatment satisfaction (both p<0.001). Two mild treatment-related AEs were recorded. Both patients recovered without sequelae and completed the study. CONCLUSIONS: Peroneal eTNM® proved to be a highly effective and safe method for the home treatment of OAB, providing a therapeutic response in approximately 80% of patients.
Keywords: Urination; Peroneal nerve; Urinary Incontinence; hyperaktivní močový měchýř; Peroneal electrical transcutaneous neuromodulation; Overactive bladder; Humans; výsledek terapie; Urgency; prospektivní studie; lidé; Treatment Outcome; Home-based therapy; inkontinence moči; Urinary Bladder, Overactive; močení; Prospective Studies